Konkurencyjność gospodarstw rolniczych na tle powiązań w systemach dystrybucji w Polsce - Milewski, Leonard (Farms Competitiveness Against the Background of Distribution Systems in Poland, 2006)
Competitiveness of agricultural farms represents ability to operate on the market well. The essential element of the agricultural market, where such processes take place, is pigs production. A level of farms production's competitiveness is influenced by production, scale of pigs' breeding in Poland and correlation of pigs' production with processing. In pigs' production in Poland, in comparison to the common market, a barrier of pigs' production scale and costs, which impact on pigs' production economics, should be eliminated. Moreover, systems of pigs' producers and meat processing and slaughter firms cooperation systems bring positive direct and indirect effects, such as increase of meat effectiveness and income as well as increase of their competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 123-129